2020
DOI: 10.1111/exd.14204
|View full text |Cite
|
Sign up to set email alerts
|

The dermal sheath: An emerging component of the hair follicle stem cell niche

Abstract: Hair follicles cyclically regenerate throughout adult mammalian life, owing to a resident population of epithelial hair follicle stem cells. Stem cell (SC) activity drives bouts of follicle growth, which are periodically interrupted by follicle regression and rest. These phases and the transitions between them are tightly spatiotemporally coordinated by signalling crosstalk between stem/progenitor cells and the various cell types of the microenvironment, or niche. The dermal papilla (DP) is a cluster of specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 108 publications
0
44
0
Order By: Relevance
“…Although the role of developmental signalling cues have been extensively studied in mice, few of these studies have been directly investigated in developing human skin. In addition to investigations of chemical signalling messengers, future work could elucidate the role of mechanical forces, such as dermis induced constriction forces, on human skin development in the organoid model 15,42‐45 …”
Section: Peering Inside the Black Box Of Human Skin Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of developmental signalling cues have been extensively studied in mice, few of these studies have been directly investigated in developing human skin. In addition to investigations of chemical signalling messengers, future work could elucidate the role of mechanical forces, such as dermis induced constriction forces, on human skin development in the organoid model 15,42‐45 …”
Section: Peering Inside the Black Box Of Human Skin Developmentmentioning
confidence: 99%
“…In addition to investigations of chemical signalling messengers, future work could elucidate the role of mechanical forces, such as dermis induced constriction forces, on human skin development in the organoid model. 15,[42][43][44][45] Positional patterning is another aspect of embryonic development reflected in skin organoid cultures. The human body contains a variety of skin types, specialized to anatomical locations (eg hairless glabrous skin on the palms).…”
Section: Peering In S Ide the B L Ack Box Of Human S Kin De Velopmentmentioning
confidence: 99%
“…56 Work by the Biernaskie lab further showed that the sheath itself harbours stem cells that-alongside with HFSC regeneration of the follicle-expand to replenish the dermal sheath and contribute to the dermal papilla of the re-growing anagen follicle. 57 Martino et al 58 in this issue provide a comprehensive review for this emerging niche cell type that regulates follicle regression in the hair cycle and may also serve to directly signal to progenitors and HFSCs to fulfil their functions.…”
Section: Hair Follicle S Tem Cell Smentioning
confidence: 99%
“…Right above the bulge is the sebaceous gland filled with sebocytes that release the sebum into the hair canal spanning the skin surface (Niemann & Horsley, 2012). The hair follicle is closely surrounded by the dermal sheath, a population of specialized fibroblast with a recently uncovered contractile function, important for hair follicle regression (Martino et al, 2021). Below the hair germ, there is a ball of mesenchymal cells that is known as the dermal papilla (DP), with known relevance to HFSC activation at the telogen‐to‐anagen transition (Morgan, 2014; Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the DP, another mesenchymal lineage closely associated with the hair follicle is the dermal sheath that encloses the DP at telogen and the hair follicle at anagen and catagen (Yang & Cotsarelis, 2010; Martino et al, 2021). Recent work demonstrated that the dermal sheath is made of cells with smooth muscle characteristics that contract to draw the DP upwards to bring it closer to the HFSCs, thus ensuring matrix cell apoptosis and proper hair cycle progression (Heitman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%